2008
DOI: 10.1038/msb.2008.56
|View full text |Cite
|
Sign up to set email alerts
|

Systemic multicompartmental effects of the gut microbiome on mouse metabolic phenotypes

Abstract: To characterize the impact of gut microbiota on host metabolism, we investigated the multicompartmental metabolic profiles of a conventional mouse strain (C3H/HeJ) (n¼5) and its germfree (GF) equivalent (n¼5). We confirm that the microbiome strongly impacts on the metabolism of bile acids through the enterohepatic cycle and gut metabolism (higher levels of phosphocholine and glycine in GF liver and marked higher levels of bile acids in three gut compartments). Furthermore we demonstrate that (1) well-defined m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
285
2
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 319 publications
(317 citation statements)
references
References 95 publications
19
285
2
5
Order By: Relevance
“…This effect was also observed in KK-Ay mice, which showed increased levels of CA, DCA, TCA and TDCA in liver and intestine, which were also observed in our study in cecal samples of C57J mice fed with a HFD (Watanabe et al, 2006). The patterns of TBAs can be modulated through diet, absence of bacteria, distinct microbiome community, BAs or farnesoid X receptors agonists (Claus et al, 2008;Li et al, 2010a;Swann et al, 2011;Watanabe et al, 2011). In this study, lower abundance of TBAs in cecum of C57N mice could also be explained through an increase in their deconjugation rate by specific gut bacteria that are using the sulfur-containing taurine as an energy source such as Enterobacteria or Bacteroides spp.…”
Section: Discussionsupporting
confidence: 86%
“…This effect was also observed in KK-Ay mice, which showed increased levels of CA, DCA, TCA and TDCA in liver and intestine, which were also observed in our study in cecal samples of C57J mice fed with a HFD (Watanabe et al, 2006). The patterns of TBAs can be modulated through diet, absence of bacteria, distinct microbiome community, BAs or farnesoid X receptors agonists (Claus et al, 2008;Li et al, 2010a;Swann et al, 2011;Watanabe et al, 2011). In this study, lower abundance of TBAs in cecum of C57N mice could also be explained through an increase in their deconjugation rate by specific gut bacteria that are using the sulfur-containing taurine as an energy source such as Enterobacteria or Bacteroides spp.…”
Section: Discussionsupporting
confidence: 86%
“…Finally, the cecal HF metaproteome was characterized by three enzymes (glutaredoxin, alkyl hydroperoxide and thioredoxin reductase) involved in oxidative stress responses, which may reflect adaptation to an environment with altered redox potential (Xiao et al, 2010). Holmes et al (2012) have provided evidence that the gut microbiome influences host metabolic phenotypes, based primarily on NMR studies (Claus et al, 2008;Calvani et al, 2010). However, only few papers focused on the analysis of metabolites in intestinal content (Martin et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the effects of the intestinal microbiota can be observed in diverse regions of the host. 'Top-down' systems biology using metabolic profiling of conventional mice revealed large, systemic effects of the microbial community on absorption, storage and metabolism of dietary compounds (Martin et al, 2007;Claus et al, 2008). These, and other studies, have demonstrated that host metabolism is responsive to intestinal-microbial metabolism, which provides complementary pathways for resorption and assimilation of dietary ingredients and drugs .…”
Section: Introductionmentioning
confidence: 90%